CoSe2@NiSe2 nanoarray as better and efficient electrocatalyst for overall water splitting. (6th November 2020) - Zhang, Xiaoshuang; Ding, Yangyang; Wu, Guangping; Du, Xiaoqiang
Abstract: Electrocatalytic water splitting is identified as one of the most promising solutions to energy crisis. The CoSe2 @NiSe2 materials were first prepared and in situ grown on nickel foam by typical hydrothermal and selenification process at 120 °C. The results show that the CoSe2 @NiSe2 material used as the 3D substrates electrode can maximize the synergy between the CoSe2 and NiSe2, and also exhibits high efficiency of water splitting reaction. The lower overpotential of only 235 mV is presented to attain 20 mA cm −2 compared to the benchmark of RuO2 electrodes (270 mV @ 20 mA cm −2 ). Besides, the CoSe2 @NiSe2 material also shows a remarkable improved hydrogen evolution reaction activity compared to NiSe2 (192 mV@10 mA cm −2 ) and Co precursor catalysts (208 mV@10 mA cm −2 ) individually, which a low overpotential of only 162 mV is achieved at 10 mA cm −2 . The CoSe2 @NiSe2 catalysts exhibit excellent water splitting performance (cell voltage of 1.50 V@ 10 mA cm −2 ) under alkaline conditions. It was proved that the high water splitting performance of the catalyst is attributed to high electrochemical activity area and synergistic effect. The work offers new ideas for the exploitation of synergistic catalysis of composite catalysts and adds new examples for the exploitation of efficient, better and relatively non-toxic electrocatalysts. Graphical abstract: The CoSe2 @NiSe2 catalysts exhibit excellent water splitting activity (cell voltage of 1.50 V@ 10 mA cm −2 ) under alkaline conditions. Image 1 Highlights: CoSe2 @NiSe2 is prepared by hydrothermal and selenification methods. CoSe2 @NiSe2 can serve as electrocatalytic water splitting catalysts. Our work provides new ideas for the development of composite catalysts.